Plant biotechnology - its role in improvement of spices - BABU, K NIRMAL; MINOO, D; GEETHA, S P; SAMSUDEEN, K; REMA, J; RAVINDRAN, P N; PETER, K V (The Indian Journal of Agricultural Sciences, 2013)
Spices have played a significant role in the history of civilization. Crop improvement in spices is difficult and timeconsuming due to their long pre-bearing age and other crop specific problems. Biotechnology offers novel avenues forcrop improvement of spices. This paper reviews the present status of biotechnology of spices with emphasis on the workdone in India on micropropagation and rapid clonal multiplication of high-yielding elite genotypes to generate goodquality planting material, exploiting somaclonal variation and genetic engineering techniques for crop improvement, invitroselection for resistance to biotic and abiotic stresses; in-vitro conservation for safe exchange of germplasm andproduction of flavour and volatile constituents in culture.